Efektivitas Pelaksanaan Program Satu Keluarga Satu Sarjana Oleh Baznas di Kabupaten Kampar - Nada Khairiyah; Zulkarnaini Zulkarnaini (Ministrate: Jurnal Birokrasi dan Pemerintahan Daerah, 2021)
The One Family One Undergraduate Program (SKSS) by Baznas is a scholarship for outstanding students at public and private campuses throughout Indonesia. This program prioritizes students who come from underprivileged families where one of the family members does not yet have a bachelor's level of education. This SKSS scholarship program finances students from the first semester to graduate. The purpose of this study was to determine the effectiveness of the implementation of the one-family one-graduate program by Baznas in Kampar Regency and to determine the factors inhibiting the effectiveness of the implementation of the one-family one-graduate program by Baznas in Kampar Regency. The theory used in this study is the theory of program effectiveness from Budiani which uses four indicators, namely accuracy of objectives, program socialization, program objectives, and program monitoring. The method that the researcher uses is a qualitative method using a descriptive approach. In this qualitative research, the author analyzes on the basis of research problems using data collection techniques in the form of interviews, observations and documentation. The results of this study indicate that the effectiveness of the implementation of the One Family One Bachelor program by Baznas in Kampar Regency can be seen from four indicators, namely the accuracy of Targets, Program Socialization, Program Targets, and Program Monitoring can be said to be effective. The obstacle for this program is the consistency of program implementation and also constrained by limited funds.